PENINGKATAN KEMAMPUAN MENULIS PUISI MELALUI METODE LATIHAN - ELIANA, NENENG (Jurnal Pendidikan Usia Dini, 2016)
THE EFFORTS TO INCREASE POETRY WRITING ABILITYTHROUGH PRACTICE METHOD, Action Research in 16 Panjak Common Primary School,Sahan Village, Seluas Sub-district, Bengkayang District, West Borneo Province. The purpose inthis research is to find the increase of poetry writing ability through practice method. Theresearch was conducted in 16 Panjak Common Primary School, Sahan Village, Seluas Subdistrict, Bengkayang District, West Borneo Province. The implementation of this research startedfrom February until April 2015 with 37students in the third grade of elementary schools as thesubject sampling and one as an observer. The method used in this research is action researchreferred to action research from Kemmis and Taggart, where’s the one cycle of activity consists of4 components, which are planning, action, monitoring, and reflection. This research consists of 2cycles with 6 actions. Data analysis in this paper use qualitative and quantitative data. Qualitativedata was obtain by monitoring along intervention act recorded in field research notes andmonitoring notes, while quantitative data was obtain by comparing first assessment average score(before action was given) and last assessment score (after action was given). This research findsthat there’s increasing in ability to write the poetry through practice method. With evidence thatthere’s increasing score, where in first assessment the average score is 5.87, while in the secondcycle, the average score is 9.05 out of 12. This showed an increasing average score by 26%.